Examining the Endangered / The Sumatran Rhino's Anatomy Explored with Protolabs and 3D Tech - Griffiths Laura (Bpa Worldwide, 2019)
Examining the Endangered, The Life and Times of SLS Powders, Data Acquisition, Surveying the Road Ahead, Metal Makers, The Degree of Freedom: 3D Printing Ceramics and Glass, Pushing for Performance in Polymer Powders, News, Factory Reset, Making the Next Generation, Opportunity Pending, Accelerating Design, Music to the Ears, In for a Penny, Pushing Prusa, Ongoing Quest for Wisdom.